1982
DOI: 10.1099/00222615-15-2-253
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Activity of Bacteroides Gingivalis and Bacteroides Asaccharolyticus

Abstract: SUMMARY. Culture filtrates of all eight strains of Bacteroides gingivalis and all five strains of B. asaccharolyticus were toxic for Vero cells. Cytotoxicity was in general greater with material from cultures of B. gingivalis than from B. asaccharolyticus but none of the culture filtrates from eight strains of B. melaninogenicus showed activity in this test. The toxic material was released during prolonged incubation and more detailed study of preparations from one strain indicated that it had a molecular weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

1982
1982
2004
2004

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 9 publications
2
18
0
Order By: Relevance
“…In addition, we showed that butyric acid fermented by F. varium induced mucosal cell apoptosis and caused UC-like lesions in mice (23), suggesting that this microorganism may be a pathogenic factor in UC. The toxicity of our butyric-acid containing supernatants is consistent with reports of the in vitro toxicity of butyric and propionic acids from dental plaque (24), butyric acid in culture filtrates of two Bacteroides species (25,26), and the in vivo toxicity of high butyrate concentrations in neonatal necrotizing enterocolitis (27,28).…”
Section: Bacterial Agents In Ulcerative Colitissupporting
confidence: 78%
“…In addition, we showed that butyric acid fermented by F. varium induced mucosal cell apoptosis and caused UC-like lesions in mice (23), suggesting that this microorganism may be a pathogenic factor in UC. The toxicity of our butyric-acid containing supernatants is consistent with reports of the in vitro toxicity of butyric and propionic acids from dental plaque (24), butyric acid in culture filtrates of two Bacteroides species (25,26), and the in vivo toxicity of high butyrate concentrations in neonatal necrotizing enterocolitis (27,28).…”
Section: Bacterial Agents In Ulcerative Colitissupporting
confidence: 78%
“…Cells were easily removed from culture dish and tened to float into culture medium without the use of trypsin-EDTA. These morphological findings are the same as other investigations 21,24,25) . MC3T3-E1 exposed to BGS at the dosage of 100㎕ showed rounding deformation of individual cells and displayed granule foramation in cell cytoplasm as well.…”
Section: ⅳ Discussionsupporting
confidence: 79%
“…It was previously shown that the asaccharolytic black-pigmented Bacteroides species Bacteroides gingivalis and Bacteroides asaccharolyticus affect Vero tissue culture cells (van Steenbergen et al, 1982), and that this effect is caused by butyric acid produced in the culture medium (Touw et al, 1982b). These findings have been confirmed and extended for other oral bacteria by Grenier and Mayrand (1985).…”
Section: Introductionmentioning
confidence: 53%
“…Ammonia and propionic acid each had a small additive effect. It was shown earlier that propionic acid alone affects the Vero cells only when high concentrations are present (Touw et al, 1982;Grenier and Mayrand, 1985). A. viscosus strain HG 85, which produces no butyric acid but rather much propionic acid (24 mmol/ L), has a moderate effect (Table 2).…”
Section: Methodsmentioning
confidence: 93%